An overview and comprehensive analysis of interdisciplinary clinical research in endometriosis based on trial registry - Yicong Xu; Zhengrong Deng; Fan Fei; Shengtao Zhou (iScience, 2024)
Summary: Endometriosis is a chronic multisystem disease associated with immunological, genetic, hormonal, psychological, and neuroscientific factors, leading to a significant socioeconomic impact worldwide. Though multidisciplinary management is the ideal approach, there remains a scarcity of published interdisciplinary clinical trials at present. Here, we have conducted a comprehensive analysis of the characteristics and issues of interdisciplinary trials on endometriosis based on the clinical registration database ClinicalTrials.gov. Among all 387 endometriosis trials, 30% (116) were identified as interdisciplinary, mostly conducted in Europe and North America, and fully funded by non-industrial sources. We documented growth in both patient-centered multidisciplinary comprehensive management and collaboration between fundamental biomedical science and applied medicine. However, compared to traditional obstetric-gynecological trials, interdisciplinary studies exhibited negative characteristics such as less likely to be randomized and less likely to report results. Our study provides insights for future trial investigators and may contribute to fostering greater collaboration in medical research.